Effect of spheroid bubble interface contamination on gas-liquid mass transfer at intermediate Reynolds numbers: From DNS to Sherwood numbers. (2nd February 2022) - Dani, Adil; Cockx, Arnaud; Legendre, Dominique; Guiraud, Pascal
Highlights: Data for partially contaminated bubbles hydrodynamics and transfer are givenby DNS. Critical Rec and separation angle models are proposed vs contamination angle θ cap . At intermediate Re the normalized C D * vs θ cap follows the Sadhal (1983) law for Re→0. At low Re normalized Sh* vs θ cap follows the law derived for Cd* by Sadhal (1983) . At intermediate Re Sh* vs θ cap no longer follows this law derived for Cd*. A new model for Sh* vs θ cap at intermediate Re and high Sc is proposed. Abstract: Gas–liquid mass transfer from spherical bubbles is studied by DNS for various Reynolds numbers ( 1 ⩽ Re ⩽ 300 ), Schmidt numbers ( 1 ⩽ Sc ⩽ 500 ) and bubble surface contamination degrees ( 0 ° ⩽ θ cap ⩽ 180 ° ). Computed separation angles, drag coefficients and average Sherwood numbers for both clean and fully contaminated bubbles are favorably compared to literature. For partially contaminated bubbles, a correlation giving the separation angle versus Re and θ cap is proposed. Local Sherwood numbers along the bubble interface shows a transition between clean and contaminated zones closed to the separation angle. At low Re, for θ cap < 40 °, mass transfer of the contaminated bubble can be estimated by correlations for spherical solid particles, meanwhile for θ cap > 160 °, bubbles can be assimilated to clean bubbles. For intermediate contamination levels, a normalized Sherwood number Sh ∗ from the drag Sadhal(1983) model can be used. For intermediate Re and high Sc, Sh ∗ converges to a function well correlated to the normalized drag coefficient C D ∗ by Sh lower ∗ = 1 - ( 1 - ( C D ∗ ) 2 ) 0.5 .